Factors associated with new persistent opioid use after ankle sprain: a cross-sectional analysis. Issue 5 (September 2021) - Gossett, Timothy D.; Finney, Fred T.; Hu, Hsou Mei; Waljee, Jennifer F.; Brummett, Chad M.; Walton, David M.; Talusan, Paul G.; Holmes, James R.
Abstract : Background: Chronic opioid use is a growing crisis in the United States. The authors examined the risk factors associated with new persistent opioid use in patients who had nonoperatively treated ankle sprains and offer evidence-based treatment recommendations for practitioners. Methods: A United States insurance claims database was used to select patients who underwent nonoperative treatment of an ankle sprain between January 2008 and December 2016. The authors examined opioid prescribing 1 yr before diagnosis and 6 mo after and defined new persistent opioid use as prescription fulfillment between 91 and 180 days after injury. We evaluated the effect of patient factors and amount prescribed on the likelihood of new persistent opioid use and the probability of refill within 30 days using logistical regression analysis. Results: A total opioid dose of 150 mg oral morphine equivalents (OMEs) prescribed within 7 days of diagnosis was the greatest modifiable risk factor for new persistent opioid use [adjusted odds ratio (aOR) 1.38, 95% confidence interval (CI), 1.28 to 1.49, P <0.001] and for likelihood of refill within 30 days (aOR, 2.22, 95% CI, 2.10 to 2.35, P <0.001). Additional factors included tobacco use, medical comorbidities, and certain pain and mental health disorders. Conclusions: New persistent opioid use is common in patients who had nonoperatively treated acute ankle sprains and is linked to identifiable patient and prescribing factors. Factors associated with new persistent opioid use include high initial prescribed dose, tobacco use, medical comorbidities, and certain pain and mental health disorders. These factors were also associated with a higher probability of refill. There is strong evidence-based support for the treatment of these injuries without opioids. Level of Evidence: Level III. Abstract : Supplemental Digital Content is available in the text.